Consultation Liaison Psychiatry for Covid-19 Inpatients: A Hospital Based Study - Thapa, Arati; Poudel, Binod; Shah, Ram Prakash; Bhusal, Arbind (Journal of College of Medical Sciences-Nepal, 2024)
Background The COVID-19 pandemic has had a significant impact on mental health worldwide. The effects of the pandemic on mental wellbeing have been multifaceted and varied from person to person. Neuropsychiatric symptoms have been described in the acute phase of the illness and as long-term consequences. The objective of this study is to describe the characteristics of COVID-19 patients referred to our liaison psychiatry service in College of Medical Sciences and Teaching Hospital, Chitwan, Nepal. Methods This is a hospital based cross-sectional descriptive study. This study was carried out within the Department of Psychiatry of College of Medical Sciences and Teaching Hospital, in Chitwan district of Nepal, over a period of 2 months from March 2021 to May 2021. Data from each psychiatric consultation within our consultation-liaison service were consecutively obtained during the study period. Psychiatric diagnosis was made as per the ICD-10/ DCR criteria. Data was analyzed using SPSS. Results Among 35 patients who received psychiatric consultation, the mean age of the patient was 48.91± 13.01. Majority, sixty two percent were male and from Chitwan District. The majority of the patients, around 37%, were diagnosed with anxiety disorder followed by 22.9% delirium, 11.4% acute stress reaction, 8.6% depressive illness and adjustment disorder. Conclusions This study concluded that there was a high prevalence of psychiatric illness among COVID-19 patients. Therefore, by conducting screening for psychiatric symptoms in COVID 19 patients' healthcare professionals can i entify individuals who may require additional mental health support and intervention. Early detection and intervention for psychiatric symptoms can help prevent worsening of mental health conditions, improve overall wellbeing and enhance the effectiveness of treatment.